PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE I - MEEUWEN, M. S. VAN; NOOTEBOOM, H. P.; STEENIS, C.G.G.J VAN (Research Center for Biology, 1961)
The revisions have been performed by Miss M. S. van Meeuwen (Pycnospora, Smithia, Uraria), H. P. Nooteboom (Galactia, Moghania, Rhynehosia, Stylosanthes, Zornia), and C. G. G. J. van Steenis (Cyclocarpa, Neocollettia).